Progressive Dwindling in Multiple Sclerosis: An Opportunity to Improve Care - Martin,J; Raffel,JB; Nicholas,R (PLOS One, 2016)
IntroductionIn the general ageing population, 40% of deaths occur following a prolonged trajectory of “progressive dwindling,” characterised by chronic accumulation of disability and frailty, and associated with increased dependency and reduced reserves. Those who progressively dwindle are poorly catered for by current healthcare systems and would benefit from a coordinated approach to their medical and social care, known as formative care. People with multiple sclerosis (pwMS) may be more likely to progressively dwindle, and may be appropriate targets for formative care pathways.ObjectivesTo determine the proportion of pwMS who follow a progressive dwindling trajectory prior to death. To relate trajectory to place of death, and examine what factors predict the progressively dwindling trajectory.MethodsA retrospective observational study of 582 deceased pwMS enrolled in the UK MS Tissue Bank, including death certificates and extensive clinical summaries.Results73.7% of pwMS had a “progressively dwindling” trajectory of dying. This was predicted by those who reach MS disease milestones earlier. 72.5% of pwMS died an MS-related death, which was predicted by an aggressive disease course from onset. Those who progressively dwindled were equally likely to die in hospital as those with other trajectories to death.ConclusionsThe progressively dwindling trajectory of dying is very common in pwMS, and can be predicted by earlier disease milestones. Pathways could target pwMS in these years prior to death, to improve care.